محاسبة الإيراد في القطاع الخدمي ( دراسة حالة عن المؤسسة العامة للاتصالات في سوريا) (Latakia University Journal - Economic and Legal Sciences Series, 2019)
تعد المحاسبة نظام معلومات هدفه الأساسي خدمة المؤسسات في تمكينها من إعداد تقارير مالية, مبنية على أسس وقواعد ومبادئ تفصح عن المركز المالي للمنشأة ونتائج أعمالها والتدفقات النقدية, وتساعد أيضاً في تحديد الكفاءة التي في ضوئها يتم تقييم نتائج الماضي والتخطيط للمستقبل في ظل التقديرات والدراسات المالية . وتبرز أهمية البحث في إبراز الحاجة لتطوير السياسات والإجراءات المحاسبية المتبعة في محاسبة الإيراد في المؤسسة العامة للاتصالات, نتيجة للتطورات الاقتصادية التي تشهدها سوريا في ظل الانفتاح الاقتصادي, وذلك من خلال اعتماد المعايير الدولية لإعداد التقارير المالية, والتي أصبحت مستخدمة بشكل واسع على المستوى العالمي. Accounting is an information system whose primary aim is serving establishments in enabling them to prepare financial report based on principles that show the financial status of the institution and the results of their performance and cash flow. It also helps in determining the ability through which the results of the past and planning of the future is estimated within these estimates and the financial studies. The importance of the research is to show the need for developing the accounting policies and procedures which are used for revenue accounting in Syrian Telecommunications Establishment as a result of the economic developments in Syria within the economic openness by adopting the International Financial Reporting Standards which are widely used by most companies around the world.